Unit testing in Java how tests drive the code - Link, Johannes; Frlich, Peter (San Francisco, Calif. : Morgan Kaufmann, 2003)
Software testing is indispensable and is one of the most discussed topics in software development today. Many companies address this issue by assigning a dedicated software testing phase towards the end of their development cycle. However, quality cannot be tested into a buggy application. Early and continuous unit testing has been shown to be crucial for high quality software and low defect rates. Yet current books on testing ignore the developer's point of view and give little guidance on how to bring the overwhelming amount of testing theory into practice. Unit Testing in Java represents a.
Cover; Foreword; Contents; Preface; Part l: Basic Techniques; Chapter 1. Introduction; Chapter 2. Automating Unit Tests; Chapter 3. Basic Steps of the Test-First Approach; Chapter 4. Test Ideas and Heuristics; Chapter 5. The Inner Life of a Test Framework; Chapter 6. Dummy and Mock Objects for Independence; Chapter 7. Inheritance and Polymorphism; Chapter 8. How Much Is Enough?; Part II: Advanced Topics; Chapter 9. Persistent Objects; Chapter 10. Concurrent Programs; Chapter 11. Distributed Applications; Chapter 12. Web Applications; Chapter 13. Graphical User Interfaces.
Title from title screen.
Includes link to companion web site.
Includes bibliographical references and index.
Title from website (viewed Jan. 19, 2006).
Keywords: Computer software -- Testing; Java (Computer program language).; Electronic books